The Driver Performance The Influence of Driver Commitment to the Organization, Discipline and Motivation with Compensation Moderation on the Performance of OJOL Drivers in Bekasi City - Budianto, Mamik S; Tussoleha Rony, Zahara; Richo Rianto , Muhammad; Manurung, Adler Heymas (Dinasti Publisher, 2024)
This research aims to see the influence of driver commitment to organization, discipline and motivation with compensation moderation on the performance of OJOL drivers in Bekasi City. This research uses quantitative methods. Data was collected using a survey method, using a questionnaire. The sample taken adopted the formula from Hair et al (2017) consisting of 100 respondents. Researchers use factor analysis to measure validity with Loading Vactor PLS SEM. To determine whether or not there is an influence between the two variables, the PLS SEM analysis technique is used. The results of this research show that the influence of driver commitment to the organization, discipline, motivation and compensation on driver performance based on the results of the hypothesis testing above has a p - value of 0.000 so the hypothesis is accepted, while the compensation variable cannot weaken or strengthen the variables Organizational Commitment, Discipline and Motivation for performance.